Model Reduction for Second‐Order Dynamical Systems Revisited. Issue 1 (18th November 2019) - Beddig, Rebekka S.; Benner, Peter; Dorschky, Ines; Reis, Timo; Schwerdtner, Paul; Voigt, Matthias; Werner, Steffen W. R.
Abstract: Second‐order control systems are used to describe the dynamics of mechanical and vibrational systems, and in particular, their response to excitations. In this article, we discuss model order reduction (MOR) of such systems. A particular focus is on preserving the second‐order structure and physical properties such as stability and passivity.